Peripheral Nerve Function and Lower Extremity Muscle Power in Older Men - Ward, Rachel E. (2013)
OBJECTIVE: To assess whether sensorimotor peripheral nerve function is associated with muscle power in community-dwelling older men. DESIGN: Longitudinal cohort study with 2.3 ± 0.3 years of follow-up. SETTING: One clinical site. PARTICIPANTS: Three hundred seventy-two participants at the Pittsburgh site of the Osteoporotic Fractures in Men (MrOS) Study (N = 5994, age = 77.2 ± 5.1 years, 99.5% white, BMI = 27.9 ± 3.7kg/m(2), power = 1.88 ± 0.6watts/kg). INTERVENTIONS: Not applicable. MAIN OUTCOME MEASURES: A nerve function ancillary study was performed 4.6 ± 0.4 years after baseline. Muscle power was measured using a power rig. Peroneal motor nerve conduction amplitude, distal motor latency, and mean f-wave latency were measured. Sensory nerve function was assessed using 10-g and 1.4-g monofilaments and sural sensory nerve conduction amplitude and distal latency. Peripheral neuropathy symptoms at the leg and feet were assessed by self-report. RESULTS: Adjusting for age, height, total body lean and fat mass, one standard deviation lower motor (β = −0.07, p<0.05) and sensory amplitude (β = −0.09, p<0.05) and 1.4-g (β = -0.11, p<0.05) and 10-g monofilament insensitivity (β = −0.17 both p<0.05) were associated with lower muscle power/kg. Compared to the effect of age on muscle power (β per year = −0.05 , p<0.0001), this was equivalent to aging 1.4 years for motor amplitude, 1.8 years for sensory amplitude, 2.2 years for 1.4-g monofilament detection, and 3.4 years for 10-g detection. Baseline 1.4-g monofilament detection predicted greater decline in power/kg. Short-term change in nerve function was not associated with concurrent short-term change in power/kg. CONCLUSION: Worse sensory and motor nerve function were associated with lower power/kg and are likely important for impaired muscle function in older men. Monofilament sensitivity was associated with greater decline in power/kg and screening may identify early risk for muscle function decline in late-life, which has implications for disability.